Zinc Blockade of SOS Response Inhibits Horizontal Transfer of Antibiotic Resistance Genes in Enteric Bacteria - Crane, John K.; Cheema, Muhammad B.; Olyer, Michael A.; Sutton, Mark D. (Frontiers in Cellular and Infection Microbiology, 2018)
The SOS response is a conserved response to DNA damage that is found in Gram-negative and Gram-positive bacteria. When DNA damage is sustained and severe, activation of error-prone DNA polymerases can induce a higher mutation rate than is normally observed, which is called the SOS mutator phenotype or hypermutation. We previously showed that zinc blocked the hypermutation response induced by quinolone antibiotics and mitomycin C in Escherichia coli and Klebsiella pneumoniae. In this study, we demonstrate that zinc blocks the SOS-induced development of chloramphenicol resistance in Enterobacter cloacae. Zinc also blocked the transfer of an extended spectrum beta-lactamase (ESBL) gene from Enterobacter to a susceptible E. coli strain. A zinc ionophore, zinc pyrithione, was ~100-fold more potent than zinc salts in inhibition of ciprofloxacin-induced hypermutation in E. cloacae. Other divalent metals, such as iron and manganese, failed to inhibit these responses. Electrophoretic mobility shift assays (EMSAs) revealed that zinc, but not iron or manganese, blocked the ability of the E. coli RecA protein to bind to single-stranded DNA, an important early step in the recognition of DNA damage in enteric bacteria. This suggests a mechanism for zinc's inhibitory effects on bacterial SOS responses, including hypermutation.